Effects of Slow Breathing on Heart Rate, Blood Pressure and Oxygen Saturation: a Comparative Study between Healthy Non-Yogic Adults and Yogic Adults - Amatya, Neebha; Prajapati, Rajesh; Shrestha, Ripti (Nepal Medical College Journal, 2025)
Slow breathing is an intentional practice of deep and slow breathing which helps to connect the mind and body to calm and increase mindfulness. This study aims to assess the effects of slow breathing on heart rate, blood pressure, and oxygen saturation and to compare its effects in yogic and other normal people. Sixty healthy female subjects of age group 18-40 years were taken by simple random technique and consists of two groups: (i) Yogic – healthy adults practicing yoga and meditation for at least 3 months (ii) non-yogic – healthy adults not practicing yoga and meditation. Mean values of basal pulse rate, systolic blood pressure, diastolic blood pressure, and oxygen saturation for non-yogic and yogic were observed and compared. Then after the slow breathing maneuverer the same parameters in two groups were observed and compared. This study showed that slow breathing was negatively associated with pulse rate and systolic blood pressure, and positively associated with oxygen saturation. There was significant difference in basal pulse rate (p=0.000) as well as after slow breathing pulse rate (p=0.000) between non-yogic and yogic group. Less significance is seen in basal systolic blood pressure (p=0.012) between groups while no significance after slow breathing. There was significant difference of oxygen saturation before and after slow breathing (p=0.000) between two groups. This study showed that practice of regular slow breathing helps to decrease in basal pulse rate, decrease in systolic blood pressure and increase in oxygen saturation.